Culture, Society and the Media - Bennett, Tony (Routledge, 2005)
This book discusses two related themes concerning the role and processes of mass communication in society. The first deals with questions regarding the power of the media: how should it be defined? how is it wielded and by whom? are previous approaches and answers to such questions adequate? The second theme revolves around the divisions between the liberal pluralist and Marxist approaches to the analysis of the nature of the media. These divisions have, in recent years, been fundamental to the debate concerning the understanding of the role of mass communication, and the examination of them in this book will challenge the reader to look more closely at a number of assumptions that have long been taken for granted.